Degradable thioester core-crosslinked star-shaped polymers. Issue 39 (7th September 2022) - Laurel, Matthew; MacKinnon, Daniel; Becker, Jonas; Terracciano, Roberto; Drain, Ben; Houck, Hannes A.; Becer, C. Remzi
Abstract : Degradable polymers are considered to present a promising solution to combat plastic pollution. Abstract : Degradable polymers are considered to present a promising solution to combat plastic pollution. However, many polymers are based on ester and amide bonds, which often require high temperatures and acidic/basic catalysis and hence do not easily degrade under typical environmental conditions. Thus, more readily degradable polymer structures that enable the use of milder conditions are highly sought after. Herein, degradable core-crosslinked star-shaped branched polymers have been synthesised via a two-step one-pot reversible addition–fragmentation chain transfer polymerisation. For the first time, a bifunctional thiomethacrylate crosslinker was used to prepare a range of star-shaped poly(methyl methacrylate) structures which were characterised by advanced viscometry gel permeation chromatography. The increased reactivity of thioesters over their oxoester analogues was exploited to degrade the resulting star-shaped polymers via amidation, as evidenced by the complete degradation of the crosslinked core upon heating in the presence of amines. The successful degradation of polymers containing thioesters shows the potential of thioester chemistry for producing more sustainable/degradable polymers with more complex and defined architectures.